Step-by-step explanation:x
2 + 16 x = 3
To create a trinomial square on the left side of the equation, find a value that is equal to the square of half of b .
( b 2 ) 2 = ( 8 ) 2
Add the term to each side of the equation.
x 2 + 16 x + ( 8 ) 2 = 3 + ( 8 ) 2
Simplify the equation.
Raise
8
to the power of 2 .
x 2 + 16 x + 64 = 3 + ( 8 ) 2
Simplify 3 + ( 8 ) 2 .
Tap for more steps...
x 2 + 16 x + 64 = 67
Factor the perfect trinomial square into ( x + 8 ) 2 .
( x+ 8 ) 2 = 67
Solve the equation for x .
Tap for fewer steps...
Take the square root of each side of the equation to set up the solution for x .
( x + 8 ) 2 ⋅ 1 2 = ± √ 67
Remove the perfect root factor
x + 8
under the radical to solve for x .
x + 8 = ± √ 67
Remove parentheses.
x + 8 = ± √ 67
Subtract
8
from both sides of the equation.
x = ± √ 67 − 8
The result can be shown in multiple forms.
Exact Form:
x = ± √67 − 8 x 2 + 16 x = 3
To create a trinomial square on the left side of the equation, find a value that is equal to the square of half of b .
( b 2 ) 2 = ( 8 ) 2
Add the term to each side of the equation.
x 2 + 16 x + ( 8 ) 2 = 3 + ( 8 ) 2
Simplify the equation.
Raise
8
to the power of 2 .
x 2 + 16 x+ 64 = 3 + ( 8 ) 2
Simplify 3 + ( 8 ) 2 .
Tap for more steps...
x 2 + 16 x + 64 = 67
Factor the perfect trinomial square into ( x + 8 ) 2 .
( x + 8 ) 2 = 67
Solve the equation for x .
Take the square root of each side of the equation to set up the solution for x .
( x + 8 ) 2 ⋅ 1 2 = ± √ 67
Remove the perfect root factor
x + 8
under the radical to solve for x .
x + 8 = ± √ 67
Remove parentheses.
x + 8 = ± √ 67
Subtract
8
from both sides of the equation.
x = ± √ 67 − 8
The result can be shown in multiple forms.
Exact Form:
x = ± √ 67 − 8
Decimal Form:
x = 0.18535277 … , − 16.18535277 …
x 2 + 16 x = 3
To create a trinomial square on the left side of the equation, find a value that is equal to the square of half of b .
( b 2 ) 2 = ( 8 ) 2
Add the term to each side of the equation.
x 2 + 16 x + ( 8 ) 2 = 3 + ( 8 ) 2
Simplify the equation.
Raise
8
to the power of 2 .
x 2 + 16 x + 64 = 3 + ( 8 ) 2
Simplify 3 + ( 8 ) 2 .
Raise
8
to the power of 2 .
x 2 + 16 x + 64 = 3 + 64
Add
3
and 64 .
x 2 + 16 x + 64 = 67
Factor the perfect trinomial square into ( x + 8 ) 2 .
( x + 8 ) 2 = 67
Solve the equation for x .
Take the square root of each side of the equation to set up the solution for x .
( x + 8 ) 2 ⋅ 1 2 = ± √ 67
Remove the perfect root factor
x + 8
under the radical to solve for x .
x + 8 = ± √ 67
Remove parentheses.
x + 8 = ± √ 67
Subtract
8
from both sides of the equation.
x = ± √ 67 − 8
The result can be shown in multiple forms.
Exact Form:
x = ± √ 67 − 8
Decimal Form:
x = 0.18535277 … , − 16.18535277 …
Decimal Form:
x = 0.18535277 … , − 16.18535277 …